Domain knowledge, ethical acumen, and query capabilities (DEQ): a framework for generative AI use in education and knowledge work - Pasty Asamoah; Daniel Zokpe; Richard Boateng; John Serbe Marfo; Sheena Lovia Boateng; David Asamoah; Abdul Samed Muntaka; John Frimpong Manso (Cogent Education)
The increasing reliance on Generative Artificial Intelligence (GenAI) among students and knowledge workers poses significant risks and raises integrity concerns, prompting some institutions to impose bans on its use. With scant research on a guided framework, strategies, and checklists for the utilization of GenAI, we propose a framework based on the expertise acquisition model, information retrieval theory, and deontological ethics theory, emphasizing the need for domain knowledge, query capabilities, and ethical acumen (DEQ). Using a ‘thing’ ethnography methodology with ChatGPT, we validated our framework, highlighting the importance of these competencies to mitigate risks, including the generation of factually incorrect and plagiarized content. Our findings suggest that while GenAI can drive innovation, its content should be used as a guiding tool to enhance critical thinking and reasoning, ultimately helping knowledge workers and students avoid plagiarism and maintain academic integrity. We discuss this novel framework and provide avenues for extending this study.